The role of emotions for 4 athletes in Nordic Combined in ski jumping competitions in World Cup - Moen, F.; Myhre, K.; Rasdal, V.; Vittersø, J.; Sandbakk, O. (The Sport Journal, 2017)
This study looks at how emotions were associated with ski jumping competitions in world cup for four athletes representing the Norwegian national team in Nordic combined. The athletes documented their emotional experiences during competition rounds (trial-, and competition rounds) and non-competitive episodes (the period just after the competition round). The results in this study show that there is no clear relationship between emotions and performance between- and within the different episodes among the athletes. However, both hedonic emotions and eudaimonic emotions were experienced at high levels across all the measured episodes. Eudaimonic emotions were significantly higher during competing episodes (trial- and competition round) compared with non-competing episodes. Anger and sadness were higher after both trial jumps and competing jumps, whereas the opposite pattern was found for fear: more fear was experienced during jumps than after jumps. The results are discussed in regard of applied implications and possible future research.